2015
DOI: 10.1016/j.adhoc.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficient, thermal-aware modeling and simulation of data centers: The CoolEmAll approach and evaluation results

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…We start from the description of the testbed we used, together with applied methodology and conclude with the discussion of the results. Description of the power models accuracy can be found in [21,22].…”
Section: Evaluation Of the Modelsmentioning
confidence: 99%
“…We start from the description of the testbed we used, together with applied methodology and conclude with the discussion of the results. Description of the power models accuracy can be found in [21,22].…”
Section: Evaluation Of the Modelsmentioning
confidence: 99%
“…Beitelmal et al further developed chiller and cooling tower model [8], while Demetriou et al included hydraulic modelling of the pipe network in the model of the cooling system [9]. Recently published model from Cupertino et al was focused on workload modelling [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that a significant reduction in cooling power is achieved by combining different cooling systems. In order to improve the energy efficiency in a data center, an enormous amount of attention has been focused on thermal modeling and workload scheduling [2,7,8]. Sun et al proposed a spatio-temporal analytical model to study the thermal-aware task scheduling for a set of high-performance computing applications in both heterogeneous and homogeneous data center [9,10].…”
Section: Relate Workmentioning
confidence: 99%